Antimicrobial proteins from oyster hemolymph improve the efficacy of conventional antibiotics - Kate Summer; Qi Guo; Lei Liu; Bronwyn Barkla; Sarah Giles; Kirsten Benkendorff (PLoS ONE, 2025)
Discovering new antibiotics and increasing the efficacy of existing antibiotics are priorities to address antimicrobial resistance. Antimicrobial proteins and peptides (AMPPs) are considered among the most promising antibiotic alternatives and complementary therapies. Here, we build upon previous work investigating the antibacterial activity of a semi-purified hemolymph protein extract (HPE) of the Australian oyster Saccostrea glomerata. HPE showed antimicrobial-biofilm inhibitory activity toward laboratory and clinical strains of Streptococcus pneumoniae and Streptococcus pyogenes at 4.4 and 24.1 μg/mL total protein, respectively. In combination assays, the effectiveness of conventional antibiotics (ampicillin, gentamicin, trimethoprim and ciprofloxacin) was improved between 2 to 32-fold in the presence of HPE (1–12 μg/mL) against a range of clinically important bacteria including Streptococcus spp., Pseudomonas aeruginosa, Moraxella catarrhalis, Klebsiella pneumoniae and Staphylococcus aureus. Effective HPE concentrations are comparable to AMPPs currently approved for use or in clinical trials pipelines. Proteomics analysis of HPE identified a number of proteins including abundant known AMPPs. It was non-toxic to A549 human lung cells up to 205 μg/mL, demonstrating safety well above effective concentrations. Activity was retained with storage at -80°C and ambient laboratory temperature (~24°C), but declined after treatment at either 37°C or 60°C (1 h). This study is in agreement with growing evidence that AMPPs show specificity and a high capacity for synergism with antibiotics. The discovery of HPE provides great opportunities for both pharmaceutical and aquaculture industry development.